1983
DOI: 10.1104/pp.72.4.1001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizobial Strain and Host Plant on Nitrogen Isotopic Fractionation in Legumes

Abstract: Lotus pedculatus L., Medicago sativa L., Macroptilwum atropwrpureum, Glycine max, and Trifoliun repens L. were grown in a N-free medium and inoculated with one of ten Rhizobium strains. Dry matter, N content, and 8"N values were determined for various plant parts.Nodules, with the exception of those from lucerne, were enriched in 1"N relative to atmospheric N. Considerable variation was found in 81"N values of plant herbage (-4.5 to +0.8). The extent of isotopic discrimination was dependent on both the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 17 publications
3
34
1
1
Order By: Relevance
“…Furthermore, the nodules were found to be strikingly enriched in 15N compared with other plant parts (SHEARER et al 1982;STEELE et al 1983;TURNER and BERGERSEN 1983;YONEYAMA et al 1984) and the enrichment increased with time during the growing season. This is probably the reason for the high ~SN value (about +7.3 0/o0) of the root+nodule component in our experiment.…”
Section: Nitrogen Yiem and ~15n Valuesmentioning
confidence: 99%
“…Furthermore, the nodules were found to be strikingly enriched in 15N compared with other plant parts (SHEARER et al 1982;STEELE et al 1983;TURNER and BERGERSEN 1983;YONEYAMA et al 1984) and the enrichment increased with time during the growing season. This is probably the reason for the high ~SN value (about +7.3 0/o0) of the root+nodule component in our experiment.…”
Section: Nitrogen Yiem and ~15n Valuesmentioning
confidence: 99%
“…against ^''N (Table 1). Several authors have demonstrated that the fractionation during Nj-fixation is influenced by the bacterial strain (Steele et aL, 1983;Bergersen et aL, 1986;Ledgard, 1989), snd Ledgard (1989) provided evidence that nutrient supply and soil moisture also influence the fractionation factor.…”
Section: Specific Processes {A) N Mineralizationmentioning
confidence: 99%
“…Such distribution was expected due to fractionation of 15 N and 14 N isotopes during transfer and reallocation of N-containing compounds to different plant parts in response to demand (see [17,18]). The relative difference in atom % 15 N excess, between the fixing and non-fixing (reference) plants, is used for determining the amount of fixed N. The atom % 15 N excess values in the reference plant were only 2% higher than in the fixing plant in the roots, but more than double for grain, husks, and stems and leaves.…”
Section: Nitrogen Derived From the Atmosphere (Ndfa)mentioning
confidence: 99%